Lymphocytic tumours of indeterminate nature: a 5-year follow-up of 98 conjunctival and orbital lesions. Issue 6 (June 1978) - Morgan, G.; Harry, J.
Abstract : Ninety-eight adnexal lymphocytic tumours of indeterminate nature have been followed up for at least 5 years. Both non-disseminating and disseminating tumours have either very similar or identical histopathological features. It is not possible to make a definitive diagnosis when the lesions are first seen, and a conclusion can be reached only after a prolonged follow-up. The nature of the non-disseminating tumours is unknown.